2000
DOI: 10.3748/wjg.v6.i6.800
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hepatitis C virus NS5 protein and genome in Chinese carcinoma of the extrahepatic bile duct and its significance

Abstract: AIM To investigate the hepatitis C virus (HCV) infection in the tissues of carcinoma of extrahepatic bile duct and study their correlation. METHODS HCV NS5 protein and HCV RNA were detected by labeled streptavidin biotin (LSAB) method and in situ reverse transcription polymerase chain reaction (IS-RT-PCR) in sections of 51 cases of carcinoma of extrahepatic bile duct and 34 cases of control group (without malignant biliary disease). RESULTSIn 51 cases of carcinoma of extrahepatic bile duct, HCV NS5 protein was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In particular, by reverse-transcriptase chain reaction assay (RT-PCR), HCV-RNA and virus replicative forms were described in different organs, such as lymph nodes, thyroid, spleen, ovary, uterus and also pancreas [73][74][75]. In 2000 Yan studied paraffin-embedded autopsy extrahepatic specimens, obtained by different organs, including pancreas, in 9 subjects with severe HCV hepatitis.…”
Section: Researches On Hbv and Hcv Pancreatic Localizationmentioning
confidence: 99%
“…In particular, by reverse-transcriptase chain reaction assay (RT-PCR), HCV-RNA and virus replicative forms were described in different organs, such as lymph nodes, thyroid, spleen, ovary, uterus and also pancreas [73][74][75]. In 2000 Yan studied paraffin-embedded autopsy extrahepatic specimens, obtained by different organs, including pancreas, in 9 subjects with severe HCV hepatitis.…”
Section: Researches On Hbv and Hcv Pancreatic Localizationmentioning
confidence: 99%
“…HCV may be a more important pathogenetic factor than Hepatitis B virus (HBV) in ICC although a high prevalence of HBV infection in ICC patient and the leading cause of HCC in China [5,6]. HCV-NS5, one of HCV-encoded multiple non-structural proteins might be involved in the development of HCC and extrahepatic bile duct carcinoma [33,34]. In this study, we found that 14 of 57 (24.6%) cases were positive for HCV-NS5 and 2 (3.5%) case for HBsAg in ICC, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…HCV antigen and its replicative forms have been observed in several organs, including lymph nodes, spleen, ovary, thyroid, uterus and pancreas. [29][30][31] In spite of these initial observations, it is only in the last five years that epidemiological trials, including case/controls and prospective studies, have been performed to assess the possible association between previous or persistent HBV-or HCV-related infection and risk of pancreatic carcinoma. Most of these studies have been published between 2010 and 2012, and for the most part they were carried out in China.…”
Section: Introductionmentioning
confidence: 99%